2017
DOI: 10.21873/anticanres.11300
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Cytotoxicity of Melatonin and New-generation Anticancer Drugs Against Leukemia Lymphocytes but not Normal Lymphocytes

Abstract: The present study demonstrates specific sensitization of leukemia lymphocytes towards anticancer drugs using melatonin and clarifies the role of reactive oxygen species (ROS) for induction of apoptosis. The study covers four conventional and 11 new-generation anticancer drugs. Four parameters were analyzed simultaneously in leukemia and normal lymphocytes treated with drug, melatonin, or their combination: cell viability, induction of apoptosis, level of reactive oxygen species (ROS), and level of protein-carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 59 publications
2
43
0
Order By: Relevance
“…Melatonin in combination with doxorubicin led to reduction in ROS and protein‐carbonyl products levels and inhibition of apoptosis. These results were similar to the effects of melatonin plus everolimus and the combination of melatonin and barasertib . In contrast, a recent study observed that melatonin did not change the cytotoxicity of anticancer drugs including cyarabine, daunorubicin and etoposide in different myeloid leukemia cell types .…”
Section: Melatonin and Leukemiasupporting
confidence: 79%
See 2 more Smart Citations
“…Melatonin in combination with doxorubicin led to reduction in ROS and protein‐carbonyl products levels and inhibition of apoptosis. These results were similar to the effects of melatonin plus everolimus and the combination of melatonin and barasertib . In contrast, a recent study observed that melatonin did not change the cytotoxicity of anticancer drugs including cyarabine, daunorubicin and etoposide in different myeloid leukemia cell types .…”
Section: Melatonin and Leukemiasupporting
confidence: 79%
“…Several experimental studies have reported that melatonin has positive and protective effects on different physiological reactions and in normal bone marrow cells suggested to be effective in leukemia therapy …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin has also been shown to exert antiproliferative and cytotoxic effects on human cancers, including colorectal cancer [7], neuroblastoma [8], hepatocarcinoma [9], lung cancer [10-12], breast cancer [13], prostate cancer [14, 15], and leukaemia [16, 17]. In a gastric cancer cell line it was already shown that proapoptotic effect of melatonin could be due to activation of a Caspase-dependent pathway and inhibition of the nuclear translocation of NF-κB p65, two processes that are regulated by p38 and c-Jun N-terminal kinase (JNK) [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are a handful of published reports that indicate melatonin may have selective toxicity to cancer cells. Synergistic cytotoxicity of melatonin and anticancer drugs toward leukemia lymphocytes but not normal lymphocytes has been described [61]. Furthermore, viability of malignant cells but not their normal counterparts is reduced by melatonin [62].…”
Section: Evidence That Melatonin Slows Rate Of Cancer Progression mentioning
confidence: 99%